Vulgar myiasis - Passos, Mauro Romero Leal; Carvalho, A.V.V.; Silva, A.R.L.; Dutra, A.L.; Goulart Filho, R.A.; Barreto, N.A.; Salles, R.S.; Santos, C.C.C.; Tibúrcio, A.S.; Monteiro, A.C.S. (Brazilian Journal of Sexually Transmitted Diseases, 1997)
Myiasis is a parasitary infection caused by several types of flies. Although this infection were of simple recognition and treatment, it’s quite rare in vulvar region. This study presents a revision about myiasis and a case description of an 19-year old woman, pregnant, having trichomoniasís. candidiasís, syphilis and serum-positivity to HIV associated to vulvar myiasis.